2022
DOI: 10.3390/molecules27238182
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of Leu-Pro-Arg-Asp-Ala Pentapeptide (LPRDA) Binding to Sortase A of Staphylococcus aureus

Abstract: Sortase A (SrtA) of Staphylococcus aureus is a well-defined molecular target to combat the virulence of these clinically important bacteria. However up to now no efficient drugs or even clinical candidates are known, hence the search for such drugs is still relevant and necessary. SrtA is a complex target, so many straight-forward techniques for modeling using the structure-based drug design (SBDD) fail to produce the results they used to bring for other, simpler, targets. In this work we conduct theoretical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…With respect to our anticipated docking study the highly flexible binding pocket of SrtA is especially problematic, which has been shown by others and also agrees with our own experience from other computational studies. 42,46,47 The conformational flexibility of the substrate binding pocket was already observable in our short refinement simulation (Fig. S41†), showing that the β6/β7 loop quickly moves from the closed conformation in towards the open conformation, although a substrate mimicking peptide was present.…”
Section: Resultsmentioning
confidence: 75%
“…With respect to our anticipated docking study the highly flexible binding pocket of SrtA is especially problematic, which has been shown by others and also agrees with our own experience from other computational studies. 42,46,47 The conformational flexibility of the substrate binding pocket was already observable in our short refinement simulation (Fig. S41†), showing that the β6/β7 loop quickly moves from the closed conformation in towards the open conformation, although a substrate mimicking peptide was present.…”
Section: Resultsmentioning
confidence: 75%
“…We also showed that both prokaryotic and eukaryotic cell lines were viable under LPRDA influence and demonstrated LPRDA’s biofilm inhibitory properties. Our recent studies have revealed novel features in ligand–host interactions between LPRDA and S. aureus SrtA [ 21 ], which, in combination with the results of this study, could create a platform for more sophisticated antibacterial development. Most studies related to SrtA inhibitors and CWA proteins have been confined to a few laboratory strains.…”
Section: Introductionmentioning
confidence: 68%
“…Moreover, the authors mentioned in the experimental section that “to improve its pharmacokinetics and therapeutic efficacy, the oligopeptide was modified by PEG2000 modification and amide modification at the N- and C-termini, respectively” [ 18 ]. There were also inconsistencies in the molecular modeling of interactions of the pentapeptide LPRDA with the S. aureus SrtA active site, which prompted us to perform our own in-depth theoretical analysis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further in silico studies were done by Shulga et al . on the LPRDA peptide binding activity and key interactions to SrtA of S. aureus [103] . The results showed different binding modes with two orientations in the binding site either in reversed polypeptide sequence orientation or direct sequence order of LPRDA.…”
Section: Peptidomimetic Srta Inhibitorsmentioning
confidence: 95%